Labyrinths of peruvianness - Mendívil Nina, José (2018)
The essay aims to show the social and cultural reality of Peruvian society in the historical context, in which the loss of horizon, the consequences of the dialectical contradictions of our ideologies of the past and that is still repeated in our ‘public scene’, which We still have a way lost in the triggers, a clear example of this is that we have a society that bifurcates to carry out a project of the Republic. What is intended in this analysis is to sustain some possible solutions to our problems, that for the lost time it would seem that we should invent and create ex nihilo, to find a place to which we should go and gather all the forms of Peruvianness, from that all stories can be told and all forms of life shared, as if they were the folds and threads of a great fabric in which all attend not to wield their truths, loyalties and cultural beliefs, but to liberate their differences by stripping them of any dogmatism or ideology, something different that perhaps seems impossible to achieve, but certainly thinkable, imaginable and desirable. In saying this, I intend to suggest that the history of their acts, revolutions and rebellions, as in other aspects, be guide to the formation of a shared memory.